Wafer‐Scale Van der Waals Assembly of Free‐Standing Near Atom Thickness Hetero‐Membranes for Flexible Photo‐Detectors (Adv. Electron. Mater. 8/2021). (12th August 2021) - Shawkat, Mashiyat Sumaiya; Han, Sang Sub; Chung, Hee‐Suk; Mofid, Sohrab Alex; Yoo, Changhyeon; Jung, Yeonwoong
Abstract : Spontaneous Delamination In article 2100395, Yeonwoong Jung and coworkers report the deterministic van der Waals assembly of wafer‐scale 2D and 3D free‐standing membranes by exploring their capillary forcedriven spontaneous delamination inside water. The assembled near atom thickness 2D/3D hetero‐membranes exhibit an excellent combination of large mechanical flexibility and high photoresponsiveness at a wide range of illumination wavelength, implying high promise for futuristic opto‐electronic devices.